EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 3 SAROLANGUN - Kasmini; Rusmini; Susanti, Try (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the effectiveness of interactive learning media in Islamic Religious Education (IRE) learning at Grade VIII of SMP Negeri 3 Sarolangun. The research was motivated by the dominance of conventional, teacher-centered instructional practices that resulted in low student motivation, limited participation, and inadequate understanding of abstract religious concepts. Employing a qualitative approach with a case study design, this research involved Islamic Religious Education teachers, students, and school administrators as research participants. Data were collected through classroom observations, in-depth interviews, and documentation, and analyzed using interactive data analysis techniques consisting of data reduction, data display, and conclusion drawing. The findings indicate that the use of interactive learning media such as interactive videos, digital quizzes, and multimedia presentations contributed positively to students’ learning experiences. The implementation of interactive media enhanced students’ motivation, increased active participation, and improved their understanding of Islamic Religious Education materials. Students demonstrated higher engagement during learning activities and showed greater interest in exploring religious concepts when learning was supported by interactive digital media. Teachers also perceived interactive media as an effective tool for presenting abstract and normative religious content in a more concrete and meaningful manner. However, several challenges were identified, including limited technological facilities, varying levels of teachers’ digital competence, and time constraints in lesson preparation. Overall, this study concludes that interactive learning media are effective in improving the quality of Islamic Religious Education learning when supported by adequate infrastructure and teachers’ pedagogical readiness. The findings suggest that schools and educators should strengthen the integration of interactive media in religious instruction to create more engaging, student-centered, and meaningful learning environments.